Is dysthanasia the only obstacle to a dignified death? - Costa, Leonardo Bocchi [UNESP]; Campos, Nathalia da Fonseca [UNESP]; Marchetto, Patricia Borba [UNESP] (FapUNIFESP (SciELO), 2024)
This paper aims to show that the phenomenon of mysthanasia is an obstacle to achieving the right to a dignified death in Brazil. Traditional bioethical discussions on dignified death, influenced by the American principlist school, tend to prioritize microethical and emerging issues. Brazil’s social reality contrasts with this view, as it is characterized by hierarchies and historical processes of social exclusion, factors that contribute to the phenomenon of miserable and unassisted death. Given this context, the study discusses the need to expand the debate on dignified death to include persistent macroethical issues and address the impact of social exclusion on the dying process of vulnerable populations. A deductive methodology was used to analyze the data collected from a narrative literature review and the DataSUS system.
¿Es la distanasia el único obstáculo para una muerte digna?
O único obstáculo à morte digna é a distanásia?
Keywords: Bioethics; Health services accessibility; Right to die